2012
DOI: 10.1111/j.1365-3040.2012.02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of leaf gas exchange and stable isotope signature of water‐soluble compounds along canopy gradients of co‐occurring Douglas‐fir and European beech

Abstract: Combined d C and d 18O analyses of water-soluble leaf and twig phloem material were used to determine intrinsic water-use efficiency (iWUE) and variability of stomatal conductance at different crown positions in adult European beech (Fagus sylvatica) and Douglas-fir (Pseudotsuga menziesii) trees. Simultaneous gas exchange measurements allowed evaluation of the differences in calculating iWUE from leaf or phloem water-soluble compounds, and comparison with a semi-quantitative dual isotope model to infer variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 65 publications
6
25
1
Order By: Relevance
“…for poplar35 and eucalyptus36, was furthermore revealed by provenance-specific variation in discrimination against stable carbon isotopes (Δ 13 C WSOM ). Δ 13 C WSOM is a time-integrated proxy of the intrinsic water use efficiency (IWUE) that exacerbates potential differences in A/g s 3738. Although the A/g s ratio was rather invariable (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…for poplar35 and eucalyptus36, was furthermore revealed by provenance-specific variation in discrimination against stable carbon isotopes (Δ 13 C WSOM ). Δ 13 C WSOM is a time-integrated proxy of the intrinsic water use efficiency (IWUE) that exacerbates potential differences in A/g s 3738. Although the A/g s ratio was rather invariable (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the collection of leaf WSOM, 75 mg twig phloem samples were soaked in 1.75 mL double demineralized water in a 2.0 mL centrifuge tube at room temperature for 24 h. According to Schneider et al . (1996) and Bogelein et al . (2012), contamination of cellular constituents dissolving into the solution is negligible during this time period.…”
Section: Methodsmentioning
confidence: 94%
“…(2004) for beech. However, Bogelein et al . (2012) found that there was 13 C enrichment in twig phloem exudates in comparison to leaf WSOM in the upper and middle beech canopy, but such enrichment was not detected in the lower shaded beech canopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations